Harrison's principles of internal medicine : companion handbook - Wilson, Jean D. ;Braunwald, Eugene ;Isselbacher, Kurt J. ;Petersdorf, Robert G. ;Martin, Joseph B. ;Fauci, Anthony S. ;Root, Richard K. (New York : McGraw Hill Education, 1991)
Only the Harrison's editors could assemble a pocket manual so complete, authoritative, and easy-to-use as this edition of Harrison's Handbook. Reflecting the same increased focused on treatment that's found in its parent text, the Handbook showcases many new treatment algorithms and tables that facilitate quick and accurate diagnosis and management of all disorders. For each condition, a concise review of pathophysiology, etiology, and clinical presentation precedes a thorough summary of diagnosis and management. New coverage includes more oncology, the latest in Alzheimer's management, state-of-the-art HIV/AIDS coverage and chapter references to the Harrison's textbook. If you can't take Harrison's with you, do the next best thing...put the Handbook in your pocket.
Section 1. Important Symptoms and Signs -- Section 2. Medical Emergencies -- Section 3. Infectious Diseases --Section 4. Cardiovascular Diseases -- Section 5. Respiratory Diseases -- Section 6. Renal Diseases -- Section 7. Gastrointestinal Diseases --Section 8. Allergy, Clinical Immunology, and Rheumatology -- Section 9. Hematology and Oncology -- Section 10. Endocrinology and Metabolism -- Section 11. Neurology -- Section 12. Psychiatric and Dependency Disorders -- Section 13. Dermatology -- Section 14. Nutrition -- Section 15. Adverse Drug Reactions -- Section 16. Laboratory Values of Clinical Importance.
Includes bibliographical references and index.
Keywords: INTERNAL MEDICINE -- HANDBOOKS, MANUALS, ETC